2018
DOI: 10.1021/acssuschemeng.8b02212
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Biomass-Derived 2(5H)-Furanone to γ-Butyrolactone over Ni-Based Bimetallic Catalysts

Abstract: 2­(5H)-Furanone was selectively hydrogenated to γ-butyrolactone (GBL) over Ni-based bimetallic catalysts, Ni-M/SiO2 (M = Fe, Co, Cu, and Zn). Catalyst characterization showed that the metal dispersion and reducibility were changed after introducing a second metal, while the physical morphology was nearly unchanged. The most active and selective bimetallic catalyst was found to be Ni–Fe/SiO2. The reaction rate constant over the 4 wt %Ni–1 wt %Fe/SiO2 bimetallic catalyst was 0.06 min–1, doubling that over 5 wt %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…The Ni–Fe/SiO 2 catalysts were synthesized by incipient wetness co-impregnation. ,, Ni­(NO 3 ) 2 ·6H 2 O (98%), Fe­(NO 3 ) 3 ·9H 2 O (98%), and SiO 2 (140 m 2 ·g –1 ) were purchased from Alfa Aesar and used without any further purification. Typically, the metallic precursors were dissolved in deionized water and then added dropwise to support SiO 2 with vigorous stirring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ni–Fe/SiO 2 catalysts were synthesized by incipient wetness co-impregnation. ,, Ni­(NO 3 ) 2 ·6H 2 O (98%), Fe­(NO 3 ) 3 ·9H 2 O (98%), and SiO 2 (140 m 2 ·g –1 ) were purchased from Alfa Aesar and used without any further purification. Typically, the metallic precursors were dissolved in deionized water and then added dropwise to support SiO 2 with vigorous stirring.…”
Section: Methodsmentioning
confidence: 99%
“…7 Ni−Fe bimetallic catalysts were also found active in hydrogenation reactions. In previous works, we reported that the Ni−Fe bimetallic catalysts, with a synergetic effect between Ni and Fe, were highly active and selective for the hydrogenation of 2(5H)-furanone 8 and furfural. 9,10 The Ni/Fe ratio was found to play a significant role, and the optimum Ni/Fe ratio was 3:1.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that these three biobased compounds derived from furfural have great synthetic and practical value. 2(5 H )‐furanone can readily be reduced to generate γ ‐butyrolactone, [30,31] a valuable biobased solvent, synthetic intermediate, and monomer for the synthesis of poly( γ ‐butyrolactone) [32] . Furfuryl alcohol is mainly used as a raw material to produce furan‐based foundry resins, [13] while hydrofuroin can be utilized as a jet‐fuel precursor [33] …”
Section: Figurementioning
confidence: 99%
“…Currently, commercial and sustainable productions of such compounds mainly focused on the synthesis of N -2­(5 H )-furanone derivatives (Figure ). Nitrogen-atom functionalities are essential motifs, and they are widely featured in diverse active ingredients found in natural and pharmaceutical products. , They consist of silicine, ervatamine, actinophyllic acid, SIRT1 inhibitor, and antitubercular agent. , One of the most common synthetic methods to produce N -2­(5 H )-furanone is through multicomponent reactions, consisting of one-pot multiple reversible steps. , …”
Section: Introductionmentioning
confidence: 99%
“…4,5 They consist of silicine, ervatamine, actinophyllic acid, SIRT1 inhibitor, and antitubercular agent. 6,7 One of the most common synthetic methods to produce N-2(5H)-furanone is through multicomponent reactions, consisting of one-pot multiple reversible steps. 8,9 Nitrogen-atom heterocycles are a typical formation of C−N bonds that remain as a challenge.…”
Section: ■ Introductionmentioning
confidence: 99%